A Novel Enzyme‐Free Biosensor for Hydrogen Peroxide Based on Black Phosphorus @Au‐Ag Nanohybrids. Issue 14 (11th April 2022) - Jian, Lishan; Fu, Hanping; Zhao, Ling; Zeng, Yating; Liu, Liran; Feng, Li; Zhang, Tianxiang; Liang, Qingshuang; Xiao, Xiufeng
Abstract: In this work, a novel BP@Au−Ag nanohybrid is fabricated by a facile ultrasonic method. A glassy carbon electrode (GCE) modified with these nanohybrids is found to be a viable enzyme‐free sensor for H2 O2 detection. The deposition of Au nanoparticles on black phosphorus (BP) nanosheets enhances the stability of the electrode. Subsequent decoration of silver nanoparticles further dramatically improves the electrochemical performance owing to the synergetic effect. The as‐prepared BP@Au−Ag/GCE displays excellent peak current response for H2 O2 reduction with a wide linear range (0.005–2.36 mM), low detection limit (1.09 μM), good stability, and negligible interference. The present work provides a new avenue for exploring novel BP‐based enzyme‐free biosensors. Abstract : Scheme 1 shows the synthetic process of BP@Au−Ag composites as a sensitive non‐enzymatic electrochemical sensor for hydrogen peroxide detection by a facile ultrasonic method. Firstly, black phosphorus was exfoliated by liquid phase method, and then doping of metal nanoparticles on BP nanosheets. Doping of metal on BP nanosheets not only increases the conductivity of the electrode, but also the electrochemical cycle stability.